2020
DOI: 10.1097/md.0000000000021045
|View full text |Cite
|
Sign up to set email alerts
|

Decisive evidence corroborates a null relationship between MTHFR C677T and chronic kidney disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 106 publications
1
3
0
Order By: Relevance
“…32 On the other hand, IL-6 can induce STAT3 phosphorylation in colon cancer cells with overexpressed RAB3C, which promotes the migration of colon cancer cells. 33 More importantly, ZC3H12B binds to the IL-6 mRNA, decreasing the production of IL-6 protein upon stimulation with IL-1b, which is in accordance with our findings. 21 Even more so, a prior study found that miR-155-5p amplified the expression of IL-6 in thyroid follicle cells and also increased the IL-6 expression in hyperlipidemia and patients with familial hypercholesterolemia.…”
Section: Discussionsupporting
confidence: 91%
“…32 On the other hand, IL-6 can induce STAT3 phosphorylation in colon cancer cells with overexpressed RAB3C, which promotes the migration of colon cancer cells. 33 More importantly, ZC3H12B binds to the IL-6 mRNA, decreasing the production of IL-6 protein upon stimulation with IL-1b, which is in accordance with our findings. 21 Even more so, a prior study found that miR-155-5p amplified the expression of IL-6 in thyroid follicle cells and also increased the IL-6 expression in hyperlipidemia and patients with familial hypercholesterolemia.…”
Section: Discussionsupporting
confidence: 91%
“…Patients in this group received GCs, and effectiveness of GCs was shown to be increased when alternative rs1801133 allele was present in children with bronchial asthma [42]. Potential protectiveness of rs1801133 variant allele in end stage renal crisis was mentioned throughout meta-analysis by Chang et al, however, results were contradictory among different populations [43]. Even though GCs were not our primary focus, this study showed that MTHFR rs1801133 might serve as a predictor of GCs response and should be further validated as such.…”
Section: Discussionmentioning
confidence: 99%
“…5E). Previous reports show that Rab3c modulates the IL6-STAT3 pathway 36 , which is critical for glucose homeostasis in hepatic tissue and skeletal muscle 37 . These results, along with their high expression of genes encoding receptors for the satiety hormones GLP-1 and leptin (Glp1r, Lepr) suggest that n11.Trh/Cxcl12 neurons may have a role in energy balance (Fig.…”
Section: Rampant Characterizes the Transcriptional Response To Metabo...mentioning
confidence: 99%